Prevalence and effect on prognosis of sarcopenia in patients with primary biliary cholangitis - Yang, Jiaqi; Jiang, Shuangshuang; Fan, Qingling; Wen, Didi; Liu, Yansheng; Wang, Kemei; Yang, Hui; Guo, Changcun; Zhou, Xinmin; Guo, Guanya; Shang, Yulong; Han, Ying (Frontiers in Medicine, 2024)
Background: Sarcopenia adversely affects the treatment outcomes in Cirrhosis and NAFLD.However, such research is limited in primary biliary cholangitis (PBC) patients. This study was performed to examine the prevalence of sarcopenia and its impact on PBC patients' prognoses.Methods: This study enrolled confirmed PBC patients who had an abdominal CT scan.Sarcopenia was determined by the L3-skeletal muscle index with a Chinese population-based cutoff value. Laboratory test values and liver stiffness measurements values were obtained from the electronic medical records.In total, 174 PBC patients with a median age of 54 (IQR,48,62) years old, were enrolled. 45 (25.9%) patients among them were diagnosed with sarcopenia. Univariate and multivariate logistic regression results illustrated that male gender (OR=9. 152, P<0.001) and LSM ≥ 12.8kPa (OR= 4.539, 95%CI= 1.651,12.478, P=0.003) were the independent risk factors of sarcopenia in PBC patients. In the prognosis analysis, sarcopenia was determined as a risk factor for indicating adverse events in PBC patients (HR=4.058, 95%CI= 1.955-8.424, P<0.001) by Cox proportional hazards regression.The current findings illustrate that comprehensive evaluation and management of sarcopenia may contribute to the improvement of treatment outcomes and life quality of PBC patients.